Pediatric Collagenous Gastroenterocolitis Successfully Treated with Methotrexate - Beate C. Beinvogl; Jeffrey D. Goldsmith; Ramalingam Arumugam; Michelle Kennedy; Mani Mokalla; Paul A. Rufo; Menno Verhave (Case Reports in Pediatrics)
A two-and-one-half-year-old previously healthy female presented with a ten-week history of watery diarrhea, nonbilious and nonbloody emesis, and low-grade fevers. She was found to have severe hypoalbuminemia and hypogammaglobulinemia. Her symptoms persisted, and she became dependent on parenteral nutrition. Biopsies obtained during subsequent endoscopic and colonoscopic studies revealed findings consistent with collagenous gastroenterocolitis. She responded to an empiric course of prednisone, but her symptoms recurred shortly after transitioning to oral budesonide. After successful reinduction with intravenous prednisone, intramuscular methotrexate was initiated. She remained asymptomatic during a 15-month course of therapy, and she continued to do well clinically until approximately nine months after weaning off methotrexate. At that point, she experienced a recurrence of diarrhea, and repeat endoscopic evaluation confirmed collagenous colitis. This responded nicely to a short course of oral budesonide, and she has since remained asymptomatic and off any therapy.